1976
DOI: 10.1159/000122484
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Thyrotropin Releasing Hormone after Binding and Stimulation of Prolactin Release by GH3 Cells. Evidence for Release of Unmodified [<sup>3</sup>H] TRH

Abstract: GH3 cells which had been exposed for 30 min to [3H]-TRH and had performed their maximum biological response, i.e. increase of prolactin (PRL) release, retained intracellular radioactivity which consisted of chemically unmodified TRH (>93%). Such preloaded GH3 cells were found able to spontaneously release into the culture medium a radioactive material [3H]-RM) which was analyzed. The kinetics of binding of [3H]-RM to intact GH3 cells and competition with unlabeled TRH were indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Indeed previous analysis by thin layer chromatography of tritiated material associated to intact cells exposed for increasing durations to ('H)TRH revealed a very slow rate of degradation: 5% after 2 h. 30% after 20 h. In addition, the radioactive material which remains associated to the cells after I h of postincu bation at 37 °C following ('H)TRH uptake for 30 min to 20 h consisted mostly of TRH (91 and 82%, respectively) ■ [13]. Moreover, the pituitary enzymes which degrade TRH have an optimal pH of activity at 7.4 and are localized both in particulate and soluble fractions [1], There are thus very few chances that they may be affected by chloroquine.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed previous analysis by thin layer chromatography of tritiated material associated to intact cells exposed for increasing durations to ('H)TRH revealed a very slow rate of degradation: 5% after 2 h. 30% after 20 h. In addition, the radioactive material which remains associated to the cells after I h of postincu bation at 37 °C following ('H)TRH uptake for 30 min to 20 h consisted mostly of TRH (91 and 82%, respectively) ■ [13]. Moreover, the pituitary enzymes which degrade TRH have an optimal pH of activity at 7.4 and are localized both in particulate and soluble fractions [1], There are thus very few chances that they may be affected by chloroquine.…”
Section: Discussionmentioning
confidence: 85%
“…Using autora diography of 1 -¡im thick sections of araldite-embedded cells as well as fractionation methods, we have previously shown that in these conditions TRH is internalized up to the nu cleus without being degraded [3,13]. Moreover, when intact GH3 cells previously loaded at 37 °C with (3H)TRH and thoroughly washed on ice were postincubated at 37 °C, un modified (3H)TRH dissociated from the cell with a half time value of 20 min [10,13]. At present, the mechanisms which are involved in TRH internalization and release are, nevertheless, completely unknown.…”
mentioning
confidence: 99%
“…The data concerning the analysis of tritiated material associated to intact cells (8) indicated that early biological response was induced by intact TRF. The existence of a continuous flow of TRF molecules on both sides of plasma membrane was suggested.…”
Section: 5) the Penetration Of Unmodified 3h-trf In Intact Cells Wasmentioning
confidence: 99%
“…2 ) confirms the presence of tritiated material (3) in the cell at both cytoplasmic and nuclear levels, without specific concentration on the plasma membrane. The tritiated material was identified as 'H-TRF (8) in the same experimental conditions. Contrary to the previous experiments reported (3) the relatively short time of exposure allowed here a very low background and an excellent quality of the autoradiographs.…”
mentioning
confidence: 99%
“…The radioactivity released into the medium was intact [3H]TRH as shown by t.l.c. [16]. In addition, the recycled material had the binding-affinity charac-Abbreviations used: HBSS/Ca2+, Hepes-buffered salt solution plus 0.5 mM Ca2+; MeTRH, 3-methyl-his-TRH; NTA, nitrilotriacetic acid; RL, receptor-4igand complex; Tf, transferrin; TRH, thyrotropin-releasing hormone; TRHR, thyrotropin-releasing hormone receptor.…”
Section: Introductionmentioning
confidence: 99%